Longitudinal Tracking of Immune Responses in COVID-19 Convalescents Reveals Absence of Neutralization Activity Against Omicron and Staggered Impairment to Other SARS-CoV-2 Variants of Concern - Odak, Ivan; Schultze-Florey, Christian R.; Hammerschmidt, Swantje I.; Ritter, Christiane; Willenzon, Stefanie; Friedrichsen, Michaela; Ravens, Inga; Sikora, Ruth; Bayir, Lâle M.; Gutierrez Jauregui, Rodrigo; Bernhardt, Günter; Stankov, Metodi V.; et al. (Frontiers in Immunology, 2022)
Evaluating long-term protection against SARS-CoV-2 variants of concern in convalescing individuals is of high clinical relevance. In this prospective study of a cohort of 46 SARS-CoV-2 patients infected with the Wuhan strain of SARS-CoV-2 we longitudinally analyzed changes in humoral and cellular immunity upon early and late convalescence. Antibody neutralization capacity was measured by surrogate virus neutralization test and cellular responses were investigated with 31-colour spectral flow cytometry. Spike-specific, isotype-switched B cells developed already during the disease phase, showed a memory phenotype and did not decrease in numbers even during late convalescence. Otherwise, no long-lasting perturbations of the immune compartment following COVID-19 clearance were observed. During convalescence anti-Spike (S1) IgG antibodies strongly decreased in all patients. We detected neutralizing antibodies against the Wuhan strain as well as the Alpha and Delta but not against the Beta, Gamma or Omicron variants for up to 7 months post COVID-19. Furthermore, correlation analysis revealed a strong association between sera anti-S1 IgG titers and their neutralization capacity against the Wuhan strain as well as Alpha and Delta. Overall, our data suggest that even 7 month after the clearance of COVID-19 many patients possess a protective layer of immunity, indicated by the persistence of Spike-specific memory B cells and by the presence of neutralizing antibodies against the Alpha and Delta variants. However, lack of neutralizing antibodies against the Beta, Gamma and Omicron variants even during the peak response is of major concern as this indicates viral evasion of the humoral immune response.